(untitled) (Nonconventional Technologies Review, 2020)
The idea of comfort arose from a history of environmental, social, psychological, and technical constraints, as a human attitude and effort to minimize these constraints and then to enhance other elements that could guarantee a different level of quality of life. In the last two decades, the efforts made to reveal factors, together with their weaknesses, which contribute to the achievement of comfort in different types of buildings considered isolated or in relation to others in rural or urban settings, can be perceived to be intensified and placed in a structured format to be considered. While comfort is important for man in any area, certain aspects of it can diminish the dynamism of evolutionary processes in humans, always tempted by the nonconventional. From this viewpoint, the limits, and weaknesses of the definition of comfort must be considered by research and the niche in which it is efficient and optimal in deciding its conditions must be preserved. The analysis implemented in this paper introduces other aspects and knowledge that can open new theoretical and research horizons in relation to the comfort of the human being and other living systems, thereby extending the limits of the notion to the concept.